FORMULATION AND IMMUNOSTIMULANT STABILITY POLYSACCHARIDE SYRUP OF FRACTION NONI (MORINDA CITRIFOLIA L.) FRUITS - S., Ediati; Saifullah, T. N.; R., Rumiyati; M. M., DUNSTANIA; P., MARIA QUEEN; S., ERNA MARIANA (International Journal of Applied Pharmaceutics, 2019)
Objective: The study aimed to formulate standardized polysaccharide fraction of Noni (SPFN) fruit into syrup preparations to fulfill the acceptability requirement of National Agency of Drugs and Food Control [Badan Pengawas Obat dan Makanan Republik of Indonesia (BPOM RI)] so that it can be used in the community as an immunostimulant. Methods: The optimization of the formula A and B were done using Simplex Lattice Design (SLD) method and its stability tested under extreme temperature change effect using thaw cycling method by evaluating the physical properties, microbial contamination and immunostimulant activity. MTT method was used to determine the immunostimulant activity of syrup against lymphocyte proliferation in vitro. Results: Based on the results of stability tests of formula A using pH (4.45), viscosity (81.03 mPas), taste (good taste), pouring power (2.31 s), amount of bacteria (68 colonies/ml), total yeast and mold (269 colonies/ml) parameters and fulfilled the acceptability requirement of BPOM RI. Formula A could maintain better stability than formula B. Formula A syrup used for immunostimulant activity testing that could increase lymphocyte proliferation at a concentration of 13.33 to 106.64 μg/μl and it’s stable under the influence of extreme temperature changes. Conclusion: Formula A could be used to produce SPFN syrup, which has stable physical properties and immunostimulant activity beside no microbial contamination that fulfill requirements of BPOM RI.